THE CHALLENGES AND PECULIARITIES IN THE TRANSLATION OF RELIGIOUS TERMINOLOGY - Abdualimova Lobar G'aybulla qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the challenges and specific features associated with the translation of religious texts. Religious texts possess unique linguistic, cultural, and contextual characteristics that pose particular difficulties for translators. The study examines the semantic, stylistic, and pragmatic nuances that require careful consideration during translation processes. The research identifies common issues faced by translators, such as preserving sacred meanings, interpreting metaphors, and conveying doctrinal concepts accurately. The article also highlights the importance of balancing literal fidelity with interpretative clarity in religious translation.